Maximal Ratio Combining Using Channel Estimation in Chaos Based Pilot-Added DS-CDMA System with Antenna Diversity - Patel, Meher Krishna; Berber, Stevan M.; Sowerby, Kevin W. (Wireless Communications and Mobile Computing, 2017)
This paper presents an adaptive multiuser transceiver scheme for DS-CDMA systems in which pilot symbols are added to users’ data to estimate complex channel fading coefficients. The performance of receiver antenna diversity with maximal ratio combining (MRC) technique is analyzed for imperfect channel estimation in flat fading environments. The complex fading coefficients are estimated using least mean square (LMS) algorithm and these coefficients are utilized by the maximal ratio combiner for generating the decision variable. Probability of error in closed form is derived. Further, the effect of pilot signal power on bit error rate (BER) and BER performance of multiplexed pilot and data signal transmission scenario are investigated. We have compared the performance of added and multiplexed pilot-data systems and concluded the advantages of both systems. The proposed CDMA technique uses the chaotic sequence as spreading sequence. Assuming proper synchronization, the computer simulation results demonstrate the better bit error rate performance in the presence of channel estimator in the chaotic based CDMA system and the receiver antenna diversity technique further improves the performance of the proposed system. Also, no channel estimator is required if there is no phase distortion to the transmitted signal.